INTEGRASI MEDIA SOSIAL DALAM PEMBELAJARAN GENERASI Z - Awal Kurnia Putra Nasution (Jurnal Teknologi Informasi dan Pendidikan, 2020)
Advances in information technology have now penetrated all sectors in the world of education, including teachers and students. Students who are currently the Generation z are very active in using social media, from the fact the author feels the need to integrate social media into Generation z learning. This article will discuss what social media can be integrated in generation z learning, and how to integrate it. The research methodology used is a combination of library research and the author's experience in using social media in learning. Social media that can be integrated into Generation z learning, namely Facebook, WhatsApp, Twitter and Instagram. This election is based on the popularity of social media applications among the z generation, and all z generations use it. The way to integrate social media into learning generation Z, is by utilizing social media Facebook, WhatsApp, Twitter, and Instagram as learning media. In practice this social media can be used as a virtual class, a forum for discussion, a place to share learning materials, share videos and pictures, and share information links around the lesson.